PELAKSANAAN SUPERVISI KLINIS DI SEKOLAH DASAR ISLAM - Andi Nur Alam; Achmad Supriyanto; Burhanuddin Burhanuddin (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2016)
The purpose of this study was to describe the implementation of clinical supervision in the Islamic primary school. This study used a qualitative approach with case study design. The data collection used observation interviews, and documentation The analysis used a single data with the steps of collecting, presenting and conclusion. The results showed (1) Clinical Supervision in the Islamic primary school did with the stages of pre-conference, the revised contract, classroom observation, and post-conference; (2) The problem of teachers resolved through persuasive approach, opened and communicate well; (3) The obstacles of the implementation of clinical supervision came from the bustle of the principal, the teacher's perception and factors from the students.Tujuan penelitian ini mendeskripsikan pelaksanaan supervisi klinis di Sekolah Dasar Islam. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan studi kasus. Pengumpulan data menggunakan teknik observasi, wawancara, dokumentesi. Menggunakan analisis data tunggal dengan langkah mengumpulkan, menyajikan dan penarikan kesimpulan. Hasilnya menunjukkan (1) supervisi klinis di SD Islam dilakukan dengan tahapan pre-conference, revisi kontrak, clasroom observation, dan post-conference; (2) permasalahan guru teratasi melalui pendekatan persuasif, terbuka dan berkomunikasi dengan baik; (3) kendala pelaksanaan supervisi klinis dari kesibukan kepala sekolah, persepsi guru dan faktor siswa.